Influence of Li+ doping on the optical properties of PbS. (September 2017) - Chávez Portillo, M.; Mathew, X.; Santiesteban Juárez, H.; Pacio Castillo, M.; Cortes Santiago, A.; Portillo Moreno, O.
Abstract: We investigate the influence of Li + in the optical properties of PbS thin films. PbS and PbS:Li doped films were prepared by chemical bath deposition. Optical studies using the first derivative absorption spectra reveals the multiple exciton generation process associated to the excitonic transitions. The refractive index (n), extinction coefficient (k), and dielectric parameters ( ε 1 and ε 2 ) were obtained. The analysis of current-temperature measurement in the 12–320 K range shows that the activation energy exhibits lower values with increasing Li + concentration. The mechanism of current conduction in the films is discussed. Highlights: Multiple exciton generation in PbS and PbS:Li was observed. Solid state parameters of PbS Li doping were studied. PbS:Li nanocrystals transport mechanism was discussed.